Soil Moisture Retrieval from MODIS and AMSRE Satellite Data A Case Study of Sindh Province, Pakistan - Syed Shahid Ali; Muhammad Usman Khan; Sayed Sanaullah Shah (Journal of Basic & Applied Sciences, 2015)
Sindh province has diverse agro-climatological regions ranging from irrigated agricultural belt in the middle and desert to the east and bare hilly ranges on the west. Climate of the province is semi-arid with low annual precipitation of around 200mm. Agriculture and agribusiness is the main source of livelihood for majority in the province. Soil moisture study is an important parameter in agriculture, hydrology and hydrometeorology for studies related to sustainable development of agriculture and agribusiness in the province. In agriculture, soil moisture is used to study evapotranspiration, droughts, irrigation scheduling, and crop yield forecasting. It is also important for the environmental studies like subsequent precipitation patterns, temperature change and water quality. Soil moisture plays an important role in hydrology e.g., flood control, soil erosion and slope failure, reservoir management, geotechnical engineering and runoff generation. Due to synoptic coverage and high temporal resolution satellite remote sensing is ideal for instantaneous measurement of soil moisture content and its spatial and temporal behavior. In this study soil moisture at province level has been mapped through Advanced Microwave Scanning Radiometer (AMSR-E) and Moderate Resolution Imaging Spector Radiometer (MODIS) for the years 2007 and 2010. As 2007 was as normal year while 2010 was a wet year due to heavy rainfall and flood in the province, both the years have been selected to study soil moisture anomalies in normal and wet seasons. The results of MODIS derived soil moisture is in moderate agreement with AMSR-E soil moisture product proving the effectiveness of high resolution products in optical range.